KAJIAN EFEK IKLAN DAN ADVERTORIAL PADA PENGETAHUAN DAN PERSUASI YANG DIRASAKAN : STUDI PROSES ADOPSI PANGAN FUNGSIONAL - Syahlani, M.M., Dr. Ir. Suci Paramitasari (Journal of Indonesian Economy and Business, 2007)
A laboratory experiment examines the effect of advertisement, advertorial,Jurnal Ekonomi dan Bisnis Indonesia, Vol 22 No.1 Tahun 2007and source of information on the adoption process of functional food. The treatmentlevels in this experiment were company advertisement, public advertisement,company advertorials and public advertorial. One hundred and ninety-nine researchsubjects were selected; those were the ones who served as decision makers in buyingfood for themselves or their families. The result shows that the audio visualadvertisement only increases subjective knowledge whereas printed advertorialincreases both subjective and objective knowledge. Besides, the study alsodemonstrates that advertorial increases both subjective and objective knowledge.However, this study shows that company advertisement can increase the effect ofsubjective knowledge as much as the advertorial. The study does not prove that theindependent institutions increase stronger perceived persuasion effect than thecompany as the source of communication.Keywords: advertisement, advertorial, adoption process, functional food.